Telaah Pemikiran Amira El Azhary Sonbol tentang Rekonstruksi Historiografi Perempuan Muslim dalam Konteks Dakwah - Faiziyah, Neneng Athiatul; Wibisono, M Yusuf; Muhyiddin, Asep (Tadbir: Jurnal Manajemen Dakwah, 2025)
For several decades, the historiography of women in Islamic societies has often been framed through the lenses of Orientalism, cultural reductionism, and normative assumptions about the oppression of Muslim women. Such narratives have not only shaped the production of academic knowledge but have also influenced Islamic preaching (da‘wah) practices, which frequently adopt apologetic or defensive postures in responding to issues of gender justice. This article aims to analyze the theoretical and methodological contributions of Amira El Azhary Sonbol in Beyond the Exotic: Women’s Histories in Islamic Societies as a foundation for developing Islamic da‘wah oriented toward gender justice and the recognition of women’s agency. This study employs a qualitative approach through a critical literature review of Sonbol’s work and supporting scholarship in Islamic historiography, gender studies, and contemporary Islamic da‘wah. The analysis is conducted thematically, highlighting Sonbol’s critique of Orientalist exoticism, the universalization of Western feminism, and the use of Islamic legal archives as sources for women’s social history. The findings indicate that Sonbol’s historiographical reconstruction not only enriches the methodology of historical and gender studies but also opens opportunities for developing a more transformative, contextual, and justice-oriented Islamic da‘wah, without falling into the tradition–modernity dichotomy or defensive narratives.